Computational design of deep eutectic solvent functionalized ZIF-8/biochar with high selectivity for mephedrone: Experimental validation and microscopic mechanism. (1st May 2023) - Zhu, Rong; Cao, Shurui; Tian, Jie; Luo, Mengni; You, Jiade; Chen, Zhiqiong
Abstract: Deep eutectic solvents (DESs), an innovative class of adsorbent modifiers and pore expanders, possessed millions of possible combinations that extend their application in tailor-made designs. According to the structural features of mephedrone (4-methylmethcathinone, 4MMC), a predictive virtual library comprising 20 candidates was designed to guide the screening of DESs using density functional theory (DFT). Then, three types of DES-functionalized magnetic ZIF-8/shrimp shell biochar (DMZSCs) were successfully synthesized. Batch adsorption experiments and selectivity evaluation experiments consolidated the results of computational prediction. DMZSC-B had a maximum adsorption capacity of 3104.12 μg g −1 for 4MMC, and this adsorption process was spontaneous and almost irreversible, with one 4MMC molecule anchored to 1.47 receptor sites. The remarkable adsorption originated from a synergistic coordination between suitable pore size distribution and multiple adsorption sites. DMZSC-B further exhibited a stable adsorption capacity at a wide pH and selective properties for 4MMC in the coexistence of multi-chemicals. A combination of theoretical investigations, characterizations and experiments illustrated that the adsorption mechanisms were governed by pore-filling, hydrogen bonding and π-π interaction. The selective driving forces followed the sequence of π-π interaction > hydrogen bonding interaction and the proportion contribution of the three functional groups of DMZSC-B was aromatic ring > –OH > –COOH. Graphical abstract: Image 1 Highlights: Density functional theory (DFT) was exploited to design deep eutectic solvent (DES). [BTBAC][Lac] based DES-functionalized magnetic ZIF-8/shrimp shell biochar (DMZSC-B) was successfully synthesized. Experimentally verified the selectivity of DMZSC-B for mephedrone (4-methylmethcathinone, 4MMC). Three functional groups of DMZSC-B contributed with aromatic ring > –OH >–COOH. The selective driving forces of DMZSC-B for 4MMC were as follows: π-π interaction > hydrogen bonding interaction.